Kiprah Gereja Keuskupan Ruteng Pascatambang (Studi Kasus Masyarakat Lingkar Tambang di Paroki St. Thomas Morus Robek, Keuskupan Ruteng) - Keristian Dahurandi & Benediktus Denar (Jurnal Alternatif Wacana Ilmiah Interkultural, 2021)
he Catholic Church is called to maintain the integrity of the naturalenvironment since the environment is regarded as brothers and sisters.The Catholic Church regards this call as a sacred mission. Since themining investment in Manggarai, West Flores occurred the Church ofDiocese of Ruteng has consistently rejected it. The reasons are mininginvestments damage the environment and destroy the culture of localcommunities. Breakdown of various actions of resistance, miningactivities do not exist Manggarai any more, although some MiningBusiness Permits (IUPs) have not been revoked by the government.However, the impact of mining does not necessarily disappear fromthe lives of the people around the mining sites. Based on this fact, it isan urgent call of the Catholic Church in Manggarai to assist the post-mining communities as a form of defending the poor and the suffering.To achieve this goal, this study uses qualitative methods strengthenedby the process of data analysis through collection, reduction, display,and verification of data from interviews, observations, and documentstudies. These processes are also strengthened by questionnaire dataanalyzed by descriptive statistics. The results of the study indicate thatthe Church has been present as a sacrament of salvation and is calledto keep on accompanying and healing the wounds of the residents ofthe former mining circle. These undertakings are carried out through he Church’s five tasks: liturgy, proclamation, service, fellowship, andwitnessing with various derivative activities. But the empowermentof the church is not enough. The church must consistently developalternative economic models so that the people/community areeconomically empowered without damaging the environment, adheringto the principles of sustainable development, namely the principle ofdemocracy, the principle of justice and the principle of sustainability.Thus, the empowerment carried out truly respects participation oflocal communities, restores their culture, and at the same time doesnot destroy the integrity of creation.